Discursos de psicólogos em exame psicotécnico e artigo científico: perspectiva dialógica - Barcellos, Any Lilian Maxemiuc (2009)
The study herein presented is founded on a dialogical approach of the discourse and, from a wider perspective, concerning studies which occur in the intersection of language and labor, was developed to (a) extend the comprehension of an activity developed by psychologists: the production of psychodiagnoses aiming to evaluate emotional balance; (b) offer a contribution to researchers or any other professionals whose interests fall on activities performed by psychologists. On the other hand, from a narrower perspective, its aim was to understand the role played by psychologists within two distinct spheres: the sphere where activities related to the control and prevention of traffic accidents are performed and the sphere constituted by academic and research settings. To perform such a task two texts were selected: (1) a psychodiagnosis composed by a set of documents which derive from the application of the test PMK (Miokinetic Psychodiagnosis) in an applicant to a driver´s license, by a psychologist specialized in issues related to the ability of conducting a motor vehicle, and (2) a journal article about the role played by this test in the evaluation of driver´s emotional balance, published in a journal named Boletim de Psicologia and created by a group of psychologists/researchers from Universidade de São Paulo, whose aim was to publish the result of a research previously presented in an event organized to celebrate the 50th anniversary of the test PMK. The dialogic approach implies the understanding of the bakhtinian notion of dialogism according to which each single text consists on a net of dialogues between speakers and dialogues between discourses; each dialogue would be characterized by relations based on complementarity, confrontation, mutual support or relations of any other type. The development of the analytical process of the two texts revealed that both are constituted by dialogues belonging to the economic sphere (industry and commerce), to the political sphere and to the scientific sphere, forming an intricate web of values which overlap the purpose around which the activities of the psychologists who create them turn: the control and prevention of traffic accidents